Method to produce hydrazone from hydrazide - Ibrahim, Nor Azowa; Mohd Noor, Siti Mariam; Mohamad, Noor Khairin; Yeong, Shoot Kian (2014)
The present invention provides a method to produce hydrazone from hydrazide. The method includes steps of mixing a hydrazide with an aldehyde in a reaction device, adding an organic solvent forming a mixture, stirring the mixture at a oredetermined speed and a predetermined temperature for a predetermined period of time, carrying out reaction under a reflux system wherein condenser used in the reflux system is equipped with a circulating bath forming a reaction product, cooling the reaction product at an ambient temperature after the completion of reaction, adding a non-reacting liquid to the reaction product to form a white paste produiuct, conducting filtration on the white paste product to produce a dried white-solid product, recrystallizing the dried white-solid product from dimethylformamide, adding 30 to 50 mL of an organic solvent which has been heated to a temperature of between 40C to 80C to the dried white-solid product to obtain a clear solution, adding between 5 to 15mL of a non-reacting liquid to allow formation of a white paste hydrazone and conducting filtration on the white paste hydrazone to obtain dried white-solid product.